Das römische Spielewesen in der Spätantike - Puk, Alexander (Millennium-Studien / Millennium Studies, 2014)
Daily life in Late Antiquity was heavily influenced by the tradition of Roman games. This is the first comprehensive study of the world of games in Late Antiquity, with special attention to specific forms of games in the provinces. Using both documentary and archeological sources, the author suggests new regional and chronological differentiations in the development of games.